Structural and functional adaptation of Haloferax volcanii TFEα/β. Issue 5 (4th January 2018) - Blombach, Fabian; Ausiannikava, Darya; Figueiredo, Angelo Miguel; Soloviev, Zoja; Prentice, Tanya; Zhang, Mark; Zhou, Nanruoyi; Thalassinos, Konstantinos; Allers, Thorsten; Werner, Finn
Abstract: The basal transcription factor TFE enhances transcription initiation by catalysing DNA strand-separation, a process that varies with temperature and ionic strength. Canonical TFE forms a heterodimeric complex whose integrity and function critically relies on a cubane iron-sulphur cluster residing in the TFEβ subunit. Halophilic archaea such as Haloferax volcanii have highly divergent putative TFEβ homologues with unknown properties. Here, we demonstrate that Haloferax TFEβ lacks the prototypical iron-sulphur cluster yet still forms a stable complex with TFEα. A second metal cluster contained in the zinc ribbon domain in TFEα is highly degenerate but retains low binding affinity for zinc, which contributes to protein folding and stability. The deletion of the tfeB gene in H. volcanii results in the aberrant expression of approximately one third of all genes, consistent with its function as a basal transcription initiation factor. Interestingly, tfeB deletion particularly affects foreign genes including a prophage region. Our results reveal the loss of metal centres in Hvo transcription factors, and confirm the dual function of TFE as basal factor and regulator of transcription.